Current diagnosis and management of adenomyosis in Canada: A survey of Canadian gynaecologists. Issue 2 (June 2022) - Maxim, Madalina; Dason, Ebernella Shirin; Chan, Crystal; Luketic, Lea; Li, Qixuan; Huszti, Ella; P. Sanders, Ari; Sobel, Mara
Objective: The purpose of this study was to understand how Canadian Obstetricians/Gynaecologists (OBGYNs) diagnose and manage adenomyosis. Methods: This cross-sectional study was performed via an online survey distributed to 262 OBGYNs at three Canadian universities (University of Toronto, University of Calgary, and McMaster University). Results: A total of 137 responses were obtained out of 262 OBGYNs (52.3%) with a completion rate of 98%. Adenomyosis was a diagnosis in 6%–10% of patients seen by OBGYNs. The most common clinical symptoms included heavy menstrual bleeding (HMB) (82.8%) and dysmenorrhea (91.0%). Most participants (83%) used transvaginal ultrasound (TVUS) as first-line imaging for diagnosis of adenomyosis. Many respondents (35.8%) indicated that adenomyosis was not associated with infertility or recurrent miscarriage. Treatment considerations for all patients with adenomyosis included levonorgestrel intra-uterine system (LNG-IUS) (91.8%), hysterectomy (88.8%), expectant management (85.1%), combined hormonal contraceptives (CHC) (83.6%), tranexamic acid (81.3%), gonadotropin releasing hormone (GnRH) agonists (64.2%), depo-provera (64.2%), dienogest (57.5%), and norethisterone acetate (NETA) (40.3%). Treatments for adenomyosis in patients wishing to conceive included expectant management (85.1%), tranexamic acid (79.1%), CHC (44.8%), LNG-IUS (32.8%), and GnRH agonists (35.8%). Excision of adenomyosis would only be offered by 24% of respondents. Uterine artery embolization (UAE) would not be used in the treatment of adenomyosis by 44% of respondents. Finally, 82.8% of respondents would use improvement of clinical symptoms to follow treatment success. Conclusion: Practice varies across Canada despite recent emerging evidence in the diagnosis and management of adenomyosis, highlighting the need for a clinical practice guideline on adenomyosis.